Analysis of the Mutations in the Active Site of the RNA-Dependent RNA Polymerase of Human Parainfluenza Virus Type 3 (HPIV3) - Malur, Achut G. (Gene Expr, 2018)
The large protein (L) of the human parainfluenza virus type 3 (HPIV3) is the functional RNA-dependent RNA polymerase, which possesses highly conserved residues QGDNQ located within motif C of domain III comprising the putative polymerase active site. We have characterized the role of the QGDNQ residues as well as the residues flanking this region in the polymerase activity of the L protein by site-directed mutagenesis and examining the polymerase activity of the wild-type and mutant L proteins by an in vivo minigenome replication assay and an in vitro mRNA transcription assay. All mutations in the QGDNQ residues abolished transcription while mutations in the flanking residues gave rise to variable polymerase activities. These observations support the contention that the QGDNQ sequence is absolutely required for the polymerase activity of the HPIV3 RNA-dependent RNA polymerase.